Profitability, Leverage, Liquidity and Bond Age On Bond Rating - Azizah, Intachfidul; Ady, Sri Utami (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
The rating of a bond becomes a guideline in purchasing bonds. The purpose of this study was to determine the effect of Profitability, Leverage, Liquidity, and Bond Age on Bond Ratings in Public Companies Listed on the IDX for the 2017-2018 period. The sample consisted of 34 companies using purposive sampling technique and analyzed using logistic regression data analysis. The results of this study indicate that simultaneously Profitability, Leverage, Liquidity and Bond Age have a significant effect on Bond Ratings while Profitability and Leverage partially have a significant effect on Bond Ratings, but Liquidity and Bond Age partially have no significant effect on Bond Ratings. The use of Logistics analysis is a novelty of this research because variable Y has a limited value/ordinal scale. Liquidity and bond age which are generally used as the basis for making decisions to buy bonds, in this study were not revealed as the next novelty of this research.